The Effectiveness of Using the Application of Coverage Management System (SIMPAN) at the Madya Tax Office Bekasi, West Java, Indonesia - Novianita Rulandari; Setya Haryati; Victor Van Kommer; Dwi Agustina; Diana Prihandini (Yayasan Ilomata, 2022)
The Archives Management System (SIMPAN) application is a breakthrough application innovation developed by the Bekasi Madya Tax Office to improve the performance of its employees in the context of monitoring and deepening tax revenue by improving the management and administration of taxpayer files and supervision of paying SPT (SPT) effectively and efficiently. The purpose of this study was to analyze the level of effectiveness of using the SIMPAN application. This study uses a qualitative descriptive method with data collection through observation, interviews, and documentation. The theory of effectiveness according to Campbell is used as a reference in this study. The results of the study indicate that the application of the SIMPAN application has been effectively carried out at the Bekasi Madya Tax Office.